IEFFICACY OF INDAPAMIDE AND VALSARTAN COMBINED THERAPY PATIENTS WITH ARTERIAL HYPERTENSION AND METABOLIC DISORDERS - G. A. Khamidullaeva; N. Z. Srojidinova; G. J. Abdullaeva; N. Sh. Shakirova; L. Sh. Khafizova (Евразийский Кардиологический Журнал, 2014)
Aim of the study: to study antihypertensive and organ-protective efficacy of indapamide and valsartan combined therapy hypertensive patients with high cardiovascular risk and metabolic disorders. Methods: The studyincluded 37 patients with stage I-III hypertension (ESH 2007), with an average age of 47.67±10.02 years, 48.6% men and 51.4% woman. Blood pressure was measured by Korotkov method. All patients were performed by M- and B-mode echocardiography. Flow-mediated endothelium dependent vasodilatation was measured during reactive hyperaemia due to 5 minute brachial occlusion.A 7.5 MHz highresolution ultrasound was used to measure carotid artery intimaemedia thickness (IMT). Blood lipid and glucose level, serum creatinin and uric acid level were estimated by enzyme assay method on biochemical analyzer “Daytona TM”. Results: 12-weekly combined therapy with indapamide and valsartan were shown very good antihypertensive efficacy in average daily doses 2.5 mg and 80±40.6 mg respectively, with reducing average blood pressure on 19.7±7.0% and attained goal level of BP in 92% cases. During the treatment were found significantly regress of left ventricular hypertrophy by reducing left ventricular mass index on 16.2±11.3%, effective vasoprotection, without significantly changes of metabolic disorders, which characterized indapamide and valsartan combination like metabolic neutral drug combination. Conclusion: Indapamide and valsartan combined therapy characterize with high antihypertensive, cardio- and vasoprotective efficacy andmetabolic neutrality choosing for treatment hypertensive patients with high cardiovascular risk and metabolic disorders.